Managing your time : - Davidson, Jeff (Advantage Quest Publications, 2004)
The 1-Minute Guide to Managing Your Time offers simple, practical help for busy people who need fast results. Through goal-oriented, 10-minute lessons, you learn all the skills you need to effectively use your time!